1980
DOI: 10.1128/jb.142.2.633-638.1980
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Thiobacillus novellus on mixed substrates (mixotrophic growth)

Abstract: In a mixotrophic environment, Thiobacillus novellus concurrently utilized glucose and thiosulfate but showed no stimulation of growth rate or yield. In most mixotrophic environments examined, the growth rate was lower than the heterotrophic growth rate, the extent of tbe decrease depending on the concentration and relative proportion of thiosulfate and glucose in the medium. Both thiosulfate and glucose were degraded to their most oxidized products in mixotrophic medium, yet the biomass production in this medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…We obtained the highest growth at 5 g.l −1 of thiosulfate (31.6 mM). This agrees well with the observations of Perez and Matin (1980) who studied the growth of the closely related species Thiobacillus novellus on mixotrophic media, using thiosulfate and/or glucose at different concentrations. They observed that the use of thiosulfate as an electron donor decreases the growth rate of T. novellus at any concentration tested and concluded to a negative correlation between initial thiosulfate concentration and growth rate although T. novellus utilized thiosulfate.…”
Section: Resultssupporting
confidence: 92%
“…We obtained the highest growth at 5 g.l −1 of thiosulfate (31.6 mM). This agrees well with the observations of Perez and Matin (1980) who studied the growth of the closely related species Thiobacillus novellus on mixotrophic media, using thiosulfate and/or glucose at different concentrations. They observed that the use of thiosulfate as an electron donor decreases the growth rate of T. novellus at any concentration tested and concluded to a negative correlation between initial thiosulfate concentration and growth rate although T. novellus utilized thiosulfate.…”
Section: Resultssupporting
confidence: 92%
“…Under such conditions, energy overproduction could become a serious problem if unrestricted use of the two substrates were to take place. These considerations suggest a rationale for the regulatory strategy employed by T. novellus in a mixotrophic environment, i.e., a decrease in the rate of substrate utilization and a partial uncoupling of substrate oxidation from energy generation (10). We may infer that this strategy is designed to protect the organism from excessive energy generation in an environment containing a superabundance of energy substrates.…”
Section: Resultsmentioning
confidence: 99%
“…Heterotrophic, autotrophic, and mixotrophic media used were obtained by supplementing the basal medium (7,9) with 0.4% glucose, 1% Na2S203, or both, respectively. The organism was grown with automatic pH control exactly as described previously (10).…”
Section: Materlals and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, these bacteria are apparently adaptable to different environments, i.e., autotrophic, heterotrophic, or mixotrophic conditions (Matin 1978). Studies have shown adaptive physiologic/metabolic response of T. novellus to mixotrophic environments (Leefeldt and Matin 1980;Perez and Matin 1980), but little engineering information, such as desired control mechanisms, and proper design and maintenance of biofilters for H 2 S removal is available.…”
Section: Introductionmentioning
confidence: 99%